Carbon contents design and characterization of gradient cemented carbonitrides with nano-TiN addition. Issue 6 (15th April 2017) - Xu, Shifa; Yang, Tian'en; Xiong, Ji; Yao, Jin; Wan, Weicai; Zheng, Qiwen
Abstract: Gradient cemented carbonitrides with brittle cubic phase depleted in the surface layer were prepared in the paper. This gradient material is believed to be a promising composite used as the substrate of a coated insert for machining operation. The formation of gradient layers stems from nitrogen decomposition. In this paper, nano-TiN was introduced as a nitrogen supplier, and besides it functioned as a grain growth inhibitor of (Ti, W)C cubic phase. The microstructure, fracture morphology, mechanical and magnetic properties of the gradient cemented carbonitrides with carbon contents from 6.04wt% to 6.34 wt% were investigated systematically. The results show that lattice parameters of (Ti, W)C in the transit zone increase due to more Ti solid solution when the gradient layer thickens. (Ti, W)C grains in the inner bulk are refined effectively by nano-TiN. Intergranular fracture along WC grain, transgranular fracture of (Ti, W)C grains, and the tearing of binder are found in the bulk of the gradient cemented carbonitride. When cracks encounter the gradient layer, they grow from new origins and a macroscopic boundary is formed between the gradient layer and the bulk. The transverse rupture strength is promoted with the carbon contents increased, and its stability is also increased. Additionally, the microhardness of the gradient cemented carbonitride is correlated closely with the Ti and Co distribution.